Cell adhesion molecule contactin‐associated protein 3 is expressed in the mouse basal ganglia during early postnatal stages. Issue 1 (21st September 2015) - Hirata, Haruna; Umemori, Juzoh; Yoshioka, Hiroki; Koide, Tsuyoshi; Watanabe, Kazutada; Shimoda, Yasushi
Abstract : Cell adhesion molecules play important roles in the development of the nervous system. Among the contactin‐associated protein (Caspr; also known as Cntnap) family, which belongs to the neurexin superfamily of proteins, Caspr and Caspr2 are indispensable for the formation and maintenance of myelinated nerves. In contrast, a physiological role for Caspr3 remains to be elucidated. This study examines the expression and localization of Caspr3 in the mouse brain using newly generated Caspr3 antibodies. Caspr3 was expressed abundantly between the first and the second postnatal weeks. During this period, Caspr3 was localized especially to the basal ganglia, including the striatum, external segment of the globus pallidus, and substantia nigra, and no gross abnormalities were apparent in the basal ganglia of Caspr3 knockout mice. In the striatum, Caspr3 was expressed by a subpopulation of medium spiny neurons that constitute the direct and indirect pathways. Caspr3 immunostaining was observed as punctate around the cell bodies as well as in the soma. These Caspr3 signals did not, however, overlap with those of synaptic markers. Our findings suggest that Caspr3 may play an important role in basal ganglia development during early postnatal stages. © 2015 Wiley Periodicals, Inc. Abstract : Caspr3 (also known as Cntnap3) is strongly expressed in the basal ganglia, including the striatum, external segment of the globus pallidus, and substantia nigra. The abundant expression of Caspr3 was observed between the first and the second postnatal weeks.